2007
DOI: 10.2478/s11756-007-0103-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and differential expression of an aldehyde dehydrogenase gene in rice leaves in response to infection by blast fungus

Abstract: Aldehyde dehydrogenase (ALDH) superfamily is a group of enzymes metabolizing endogenous and exogenous aldehydes. Using differential display RT-PCR and cDNA library screening, a full-length aldehyde dehydrogenase cDNA (ALDH7B7) was isolated from rice leaves infected by incompatible race of blast fungus Magnaporthe grisea. The deduced amino acid sequence consists of 509 amino acid residues and shares 74∼81% identity with those of ALDH7Bs from other plants. ALDH7B7 expression was induced by blast fungus infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…5C and E). Another study has reported that expression of OsALDH7 can be induced by blast fungus infection, ultraviolet and exogenous phytohormone application (Wu et al, 2007). These results implied that OsALDH7 might function as a converging point for multiple signal transduction pathways.…”
Section: Potential Rice Aldh Genes Involved In Plant Response To Strementioning
confidence: 95%
See 1 more Smart Citation
“…5C and E). Another study has reported that expression of OsALDH7 can be induced by blast fungus infection, ultraviolet and exogenous phytohormone application (Wu et al, 2007). These results implied that OsALDH7 might function as a converging point for multiple signal transduction pathways.…”
Section: Potential Rice Aldh Genes Involved In Plant Response To Strementioning
confidence: 95%
“…Among them, nine genes were located in six pairs of duplicated genome regions. Three ALDH (Li et al, 2000); ALDH2a ; ALDH1b and ALDH2b (Tsuji et al, 2003b); ALDH7B7 (Wu et al, 2007); BADH (Nakamura et al, 1997); P5CS (Igarashi et al, 1997 genes (OsALDH6, OsALDH7 and OsALDH11) were asymmetrically located in three duplicated block pairs, indicating the occurrence of gene loss following the gene duplication. The remaining duplicated block pairs contained ALDH genes (OsALDH2-4/OsALDH2-5, OsALDH3-4/OsALDH3-5 and OsALDH18-1/OsALDH18-2) in both duplicated regions.…”
Section: Wgd and Tandem Duplication Both Contribute To The Superfamilmentioning
confidence: 97%
“…ALDH induction has been observed in a variety of plants species exposed to heat, dehydration, salinity, oxidants, ultraviolet (UV) radiation, pesticides or metals. Mechanical trauma and fungal infection can also elicit ALDH up-regulation in plants [3]. Pathogenic bacteria encounter oxidative stress emanating from the host immune response that must be overcome during invasion and sustained infection [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…In rice, OsALDH7 is induced by various osmotic stresses (Wu et al 2007;Gao and Han 2009;Shin et al 2009). We also observed its induction by stress treatments of dehydration, salinity and ABA, especially in leaf (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 98%